Diagnostic Accuracy of Pleural Fluid Adenosine Deaminase Level Test in Tuberculous Pleural Effusion - Puspa Rosfadilla; Widirahardjo Widirahardjo; Fajrinur Syarani; Erna Mutiara (Perhimpunan Dokter Paru Indonesia (PDPI)/The Indonesian Society of Respirology (ISR), 2017)
Background: Tuberculous pleural effusion is a paucibacillary manifestation of tuberculosis, so isolation of Mycobacterium tuberculosis is difficult, biomarkers being an alternative for diagnosis. Adenosine deaminase has the potential to optimize the diagnostic approach of tuberculous pleural effusion. Methods: This study is a diagnostic test observational (cross-sectional), which included 35 inpatient samples that meet inclusion and exclusion criteria from H. Adam Malik Medan General Hospital. Research began on February 1st until July 31st 2016 to examine 10 cc of pleural fluid specimens for the levels of Adenosine deaminase. Results: There are significant differences in the levels of adenosine deaminase from tuberculous and non-tuberculous pleural effusion (P=0.001). In the cut-off point 36.55 IU/L, level of sensitivity 95.8%, specificity 90.99%, positive predictive value 95.8%, negative predictive value 90.99%, and accuracy 94.2% of pleural fluid adenosine deaminase level test in tuberculous pleural effusion. Conclusion: Adenosine deaminase pleural fluid can be a diagnostic modality that is easy, fast, relatively affordable and applicable in the diagnosis of tuberculous pleural effusion. (J Respir Indo. 2017; 37(4): 278-82)